Perlindungan Hukum Terhadap Pekerja Penambangan Pasir Ditinjau Dari Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan (Studi Kasus Di Desa Sebudi Kecamatan Selat Kabupaten Karangasem) - I Gusti Ngurah Bagus Adhiguna; Ketut Sudiatmaka; Ketut Sari Adnyani (Jurnal Pacta Sunt Servanda, 2020)
This study aims to determine the form of legal protection for sand mining workers and the factors causing the absence of legal protection for sand mining workers.This research involved sand shippers entrepreneurs and workers.This research is an empirical juridical and uses observation, document studies and interviews.The results showed that: the form of legal protection provided was below the standard and the cause of the absence of legal protection due to lack of information and socialization.